ANALISIS PERHITUNGAN NILAI OVERALL EQUIPMENT EFFECTIVENESS (OEE) DALAM MENUNJANG EFISIENSI DAN EFEKTIVITAS PROSES PADA PT ASTRA OTOPARTS TBK DIVISI NUSAMETAL - Ediyanto (Jurnal Satya Mandiri Manajemen dan Bisnis, 2015)
The research is aimed to evaluate the performance of High Pressure Die Casting (HPDC) machines in the Nusametal division of PT Astra Otoparts Tbk whether it has met the world class companyas guided by the company’s vision.The research uses descriptive approach. The quantitative analysis technique here uses Overall Equipment Effectiveness (OEE) score analysis. The result from OEE score calculation will be compared with standard OEE score for world class companies. Meanwhile, the result is also analysed qualitatively by identifying six big losses which cause downtime in HPDC process. The research data uses the Production Daily Report (LHP) for the period of January to December 2014.The data calculation concludes that the average OEE score of HPDC machines in the Nusametal division of Astra Otoparts Tbk is 61.60% which means has not met the standard of world class company yet. Based on the identification of six big losses, the machine breakdown is the major contributor (51%), followed by setup and adjustment (26%), production rejects (17%) and small stops (6%). Meanwhile, referring to the OEE category, the downtime loss is the major contributor of machine downtime (77%), followed by quality loss (17%) and speed loss (6%).